Answer:
-13, -3
15, 2.6
Step-by-step explanation:
x, y are the numbers
x = 5y + 2
x×y = 39
(5y + 2)×y = 39
5y² + 2y - 39 = 0
the solution of a quadratic equation :
y = (-b ± sqrt(b² - 4ac))/2a
a = 5
b = 2
c = -39
y = (-2 ± sqrt(2² - 4×5×-39))/2×5 =
= (-2 ± sqrt(4 + 780))/10 =
= (-2 ± sqrt(784))/10 = (-2 ± 28)/10
y1 = (-2 + 28)/10 = 26/10 = 2.6
y2 = (-2 - 28)/10 = -30/10 = -3
x1 = 5×2.6 + 2 = 13 + 2 = 15
x2 = 5×-3 + 2 = -15 + 2 = -13
We are given the data ho equal to 704 feet and vo equal to 112 feet per second. We apply then kinematics equation: h = ho + vot - 1/2 gt2. Substituting to the given equation,
h = 704 + 112t - 1/2 * 32*t2when h is equal to zero,0 = 704 + 112t - 1/2 * 32*t2t is equal to 11 seconds
58 is the angle to the answer
Answer:
<h2> 4(-1+2-3+4-5+6-7+......+1000) = 2000</h2>
Step-by-step explanation:
-1+2 = 1
-3+4 = 1
-5+6 = 1
and so on till -999+1000 = 1
1 .... 1000 - these are 1000 numbers, so
1000:2 = 500 pairs with sum equal 1
4(500•1) = 4•500 = 2000